Crystal structure of channelrhodopsin, a light-gated cation channel – all cations lead through the monomer – - Kato, Hideaki E. (Biophysics (Nagoya-shi), 2013)
Channelrhodopsin (ChR) is a light-gated cation channel derived from green algae. Since the inward flow of cations triggers the neuron firing, neurons expressing ChRs can be optically controlled even within freely moving mammals. Although ChR has been broadly applied to neuro-science research, little is known about its molecular mechanisms. We determined the crystal structure of chimeric ChR at 2.3 Å resolution and revealed its molecular architecture. The integration of structural, electrophysio-logical, and computational analyses provided insight into the molecular basis for the channel function of ChR, and paved the way for the principled design of ChR variants with novel properties.